1998
DOI: 10.3168/jds.s0022-0302(98)70124-9
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Raw Milk for Tetracycline Residues

Abstract: Navrátilová P., Borkovcová I., Dračková M., Janštová B., Vorlová L. (2009): Occurrence of tet-racycline, chlortetracycline, and oxytetracycline residues in raw cow's milk. Czech J. Food, Sci., 27: 379-385. The objective of this study was the detection of tetracycline, chlortetracycline and oxytetracycline residues in raw cow's milk. When analysing bulk milk (n = 57) and tanker trailer'a (n = 113) samples, two methods were used simultaneously: a specific rapid test Milk Tetrasensor Kit and high performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 2 publications
0
14
0
3
Order By: Relevance
“…[28]. Milk was heated for 10 min at 80℃ and centrifuged at 10000 r/min for 25 min to separate protein and grease.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…[28]. Milk was heated for 10 min at 80℃ and centrifuged at 10000 r/min for 25 min to separate protein and grease.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Besides, their degradation products are also toxic to some degree [17] . Furthermore, because of the complexation of tetracycline with Ca 2+ [18] , relatively high level of antibiotic residues enrich in the animal bones when animals are bred with tetracycline in a long period [19] , as well as in fish [4,20] , meat [21][22][23] , eggs [24][25][26][27] and milk [28,29] . Therefore, the detection of tetracycline is closely linked to human life.…”
mentioning
confidence: 99%
“…The false-positive results of the Charm HVS test for tetracyclines may be related to the fatty acid content of raw milk samples (2,5). In an earlier study (15), it was shown that tetracycline residue concentrations found with the Charm test at levels below 150 ng/ml should be considered with reservation. Moreover, we clearly demonstrated that UHT and/or Charm reference milk is not suitable for use as the reference blank sample for Charm HVS tests for tetracyclines ( Table 2).…”
Section: Quinolones and Polymyxinsmentioning
confidence: 99%
“…El "Sistema Microbiológico Multiresiduo o Multiplaca" (SMMP) que ha sido descrito por Nouws et al (1998Nouws et al ( , 1999a, consiste en la preparación de 7 placas de Petri (140 mm de diámetro) con 6 microorganismos cuyas características aparecen reflejadas en el Cuadro 15. En este cuadro se muestra con detalle los microorganismos empleados (formas esporuladas y vegetativas), su concentración, la composición y pH de los medios de cultivo, la temperatura y tiempo de incubación, así como los residuos objeto de detección en las distintas placas.…”
Section: Sistema Microbiológico Multiplaca (Smmp)unclassified
“…También, Nouws et al (1998) cuando utilizan Bacillus cereus ATCC 11778 como sensor biológico, observan halos de inhibición mayores para muestras que contienen 10 µg/kg de doxiciclina (32,3 mm) o clortetracilina (29,9 mm), que en muestras enriquecidas con 30 µg/kg de oxitetraciclina (22,2 mm) o tetraciclina (22,6 mm), poniendo de manifiesto la mayor sensibilidad de este microorganismo para detectar residuos de doxiciclina y clortetraciclina en leche que el resto de tetraciclinas.…”
Section: Detección De Cefalosporinasunclassified